2021
DOI: 10.1007/s42452-021-04333-w
|View full text |Cite
|
Sign up to set email alerts
|

Parallel machines scheduling with time-dependent deterioration, using meta-heuristic algorithms

Abstract: In this paper, we consider the identical parallel machines scheduling problem with exponential time-dependent deterioration. The meaning of time-dependent deterioration is that the processing time of a job is not a constant and depends on the scheduled activities. In other words, when a job is processed later, it needs more processing time compared to the jobs processed earlier. The main purpose is to minimize the makespan. To reach this aim, we developed a mixed integer programming formulation for the problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…A genetic algorithm has been considered one of the optimization methods for solving complex problem (Guo et al, 2010). Many researchers have relied on the genetic algorithm to schedule the jobs in identical parallel machines with the goal of minimizing the total tardiness (e.g., Schaller, 2014;Shim, & Kim, 2007;Tan et al, 2019;Kim et al, 2020;Anghinolfi et al, 2021;Juybari et al, 2021). Others, such as Cheng, Gen, & Tozawa (1995) utilized the genetic algorithm to schedule n jobs in the identical parallel machines with an objective of minimizing the maximum weighted lateness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A genetic algorithm has been considered one of the optimization methods for solving complex problem (Guo et al, 2010). Many researchers have relied on the genetic algorithm to schedule the jobs in identical parallel machines with the goal of minimizing the total tardiness (e.g., Schaller, 2014;Shim, & Kim, 2007;Tan et al, 2019;Kim et al, 2020;Anghinolfi et al, 2021;Juybari et al, 2021). Others, such as Cheng, Gen, & Tozawa (1995) utilized the genetic algorithm to schedule n jobs in the identical parallel machines with an objective of minimizing the maximum weighted lateness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The functional deterioration of disassembly tools is one of them. Tool deterioration causes the actual processing time of disassembly tasks to grow longer over time [15][16][17]. Some studies are reported that consider tool deterioration in manufacturing systems.…”
Section: Introductionmentioning
confidence: 99%